Why prospective migrants aren’t morally obliged to comply with immigration law - Christofidis, M (2024)
Each year, hundreds of thousands of prospective migrants act in contravention of states’ immigration law. Despite this, little philosophical attention has been paid to the question of whether or not prospective migrants are morally required to comply with immigration law. In this essay, I argue that prospective migrants are not morally obliged to comply with immigration law. In sections 1-3, I argue that prospective migrants are not under political obligations to comply with immigration law. In section 1, I demonstrate that the natural duty of justice does not bind prospective migrants to comply with immigration law. This is because individuals are under natural duties of justice to comply with only those just institutions which apply to them. As I demonstrate, however, while the natural duty of justice applies to prospective migrants in the sense that it is addressed to them, it does not apply to them in the sense required for grounding the natural duty of justice. In section 2, I argue that prospective migrants are not under obligations of fair play to comply with immigration law because immigration law fails to constitute a cooperative scheme. In section 3, I argue that prospective migrants do not, in general, have obligations grounded in consent to comply with immigration law as they do not consent, either tacitly or expressly, to comply with immigration law. Then, in section 4, I argue that prospective migrants do not have moral obligations to comply with immigration law grounded in either (1) Blake’s argument from the right against unwanted obligations, (2) Wellman’s argument from the right to freedom of association, (3) Yong’s argument from the right to political independence or (4) arguments from the harms imposed by immigration on a state’s members. Finally, I conclude that (a) irregular migrants are not, in virtue of their status as irregular migrants, appropriate objects of reactive attitudes such as blame and resentment and (b) members of a state are morally permitted to help prospective migrants enter the state via irregular channels when they are doing so on grounds of necessity.